Soleus Muscle as a Surrogate for Health Status in Human Heart Failure - Green, D.; Panizzolo, F.; Lloyd, D.; Rubenson, J.; Maiorana, Andrew (2016)
We propose the hypothesis that soleus muscle function may provide a surrogate measure of functional capacity in patients with heart failure. We summarize literature pertaining to skeletal muscle as a locus of fatigue and present our recent findings, utilising in vivo imaging in combination with biomechanical experimentation and modelling, to reveal novel structure-function relationships in CHF skeletal muscle and gait.